Raise hell [videorecording (DVD)] : the life & times of Molly Ivins - Engel, Janice; Engel, Janice; Engel, Janice; Ivins, Andy; Maddow, Rachel; Rather, Dan (Magnolia Home Entertainment, 2019)
A biography of journalist Molly Ivins.